The concept of fraction: the frame of local wisdom, Al-Qur'an, and Hadith - Dewi Rosikhoh; Zainuddin Syarif; Liny Mardhiyatirrahmah (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
Culture was the case that needed to be protected, but on the other hand, many of the current generations did not know their own culture. This research explored the fraction concept used by the Madurese people, especially Pamekasan, and its relation to the fraction concept in the Al-Qur’an and hadith. This research was qualitative research with an ethnographic approach to explore information related to the fraction concept within the framework of Madurese society. The data collection techniques used interviews and documentation. Furthermore, a literature review was carried out to examine the fraction concept in the Al-Qur’an and hadith. The research results showed 6 fraction numbers found in Madurese culture, especially Pamekasan, 13 in the hadith, and 8 in the Al-Qur’an. Additionally, there were local measuring units, local measuring instruments, and local currency units that contained fraction numbers when converted to other units or international units. In this way, the discovery of the fraction concept within the framework of Madurese society, especially Pamekasan, could be developed and internalized in learning fractions in the classroom.